2021
DOI: 10.3390/s21165644
|View full text |Cite
|
Sign up to set email alerts
|

Compression Garments Reduce Soft Tissue Vibrations and Muscle Activations during Drop Jumps: An Accelerometry Evaluation

Abstract: Objectives: To explore the effects of wearing compression garments on joint mechanics, soft tissue vibration and muscle activities during drop jumps. Methods: Twelve healthy male athletes were recruited to execute drop jumps from heights of 30, 45 and 60 cm whilst wearing compression shorts (CS) and control shorts (CON). Sagittal plane kinematics, ground reaction forces, accelerations of the quadriceps femoris (QF), hamstrings (HM) and shoe heel-cup, and electromyography images of the rectus femoris (RF) and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Both of them are hip flexor muscles, we then speculate that the decrease in peak hip flexion angle and the increase of peak hip extension angle during the stance phase may be related to the decrease of flexor muscle activation weights in SYN6. On the other part, in a prior study, wearing CGs resulted in a decrease in thigh muscle activation during landing, while concurrently increasing the measured damping coefficient at the thigh (Deng et al, 2021). The author proposed that a portion of muscle activation during the landing phase serves the mitigating the soft tissue vibrations caused by the impact, and CGs may aid in this process, consequently leading to a reduction in thigh muscle activation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both of them are hip flexor muscles, we then speculate that the decrease in peak hip flexion angle and the increase of peak hip extension angle during the stance phase may be related to the decrease of flexor muscle activation weights in SYN6. On the other part, in a prior study, wearing CGs resulted in a decrease in thigh muscle activation during landing, while concurrently increasing the measured damping coefficient at the thigh (Deng et al, 2021). The author proposed that a portion of muscle activation during the landing phase serves the mitigating the soft tissue vibrations caused by the impact, and CGs may aid in this process, consequently leading to a reduction in thigh muscle activation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study have reported that wearing CGs led to a reduction in hip flexion angle and an increase in stride length during sprinting (Born et al, 2014); in a study of female athletes, CGs were found to reduce only hip abduction angle in the drop vertical jump task (Zamporri and Aguinaldo, 2018). However, previous studies have not found that CGs immediately affect kinetics during activity, such as joint force or power (Wannop et al, 2016;Deng et al, 2021). Some studies found no significant performance improvement in jumping (Berry and McMurray, 1987;Ali et al, 2010), running (Vercruyssen et al, 2014), or sprinting (Atkins et al, 2020) with CGs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research, both domestic and international, has predominantly concentrated on dissecting and explicating the kinematic and mechanical attributes of the lower extremities, encompassing the hip, knee, and ankle joints. Such studies have formulated optimized movement patterns for diverse actions through a thorough examination of pertinent indicators 38 . However, there remains a dearth of inquiries into the impact of CAI on the ankle joint biomechanics during basketball players’ execution of the three-step layup.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the use of lowercompression sportswear reduced blood lactate, blood flow, and heart rate during endurance exercises [6][7][8]. Further, participants wearing waist-to-ankle tights showed more efficient movement executions (i.e., greater muscle activations in the agonists and less hip flexion angle during sprint performances [9] and wearing compression sportswear might modulate soft tissue movements (i.e., reduced muscle oscillations) attenuating excessive impact forces [10,11]. Presumably, these physiological and biomechanical effects of compression sportswear positively influenced an individual's perceptual pain and fatigue [12].…”
Section: Introductionmentioning
confidence: 99%